Double-clad erbium/ytterbium-doped fiber laser with a fiber Bragg grating - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Tamjis, Mohamad Rom; Ahmad, Harith (IOP Publishing, 2009)
A double-clad erbium/ytterbium-doped fiber laser (EYDFL) is demonstrated using a fiber Bragg grating (FBG) as wavelength selective filter in a linear cavity resonator. The effect of the FBG's wavelength on the performance of the EYDFL is also investigated. The slope efficiencies of the EYDFL are obtained at 33.7%, 30.9%, and 24.1% for the operating wavelengths of 1553.6, 1557.3, and 1562.8 nm, respectively. The efficiency is higher with a shorter wavelength due to the amplification characteristic of the EYDF which peaks at 1545 nm. At FBG's wave-length of 1553.6 nm, the EYDFL has an output power of 520 mW when pumped at 1700 mW by a 937 nm laser diode. The laser also has a spectral bandwidth of 0.2 nm and signal to noise ratio of more than 25 dB. The threshold power to achieve lasing is measured to be approximately 90 mW for this laser.